Answer:
(-2,8)
Explanation:
To solve by substitution, first isolate a variable in one of the equations. Then, substitute the value of the variable from that equation into the other equation, giving either the x or y value of the solution. Finally, substitute that answer back into one of the two equations, finding the other missing value.
1) For both of the equations, the variable y has already been solved for. So, we can choose to substitute whatever y equals in one equation for the y in the other equation. Any choice is fine - I chose to substitute -4x for the y in y = 3x + 14.
![(-4x) = 3x + 14\\-7x = 14\\x = -2](https://img.qammunity.org/2022/formulas/mathematics/college/5kacrnrqgst0oqg9iyhp23w1ibd4wzbyjm.png)
2) Now that x has been solved for, substitute the value for the x in one of the equations. Any choice is fine here, too - I chose to substitute -2 in y = -4x:
![y = -4(-2) \\y = 8](https://img.qammunity.org/2022/formulas/mathematics/college/cj38obyucaovj5czduo2rukrfk2x336o91.png)
3) Both the x and y value of the solution has been solved for. x = -2 and y = 8. Therefore, the solution is (-2,8).